Recombinant Variants of Tissue-Type Plasminogen Activator Containing Amino Acid Substitutions in the Finger Domain - Yahara, Hitoshi; Matsumoto, Keiji; Maruyama, Hiroyuki; Nagaoka, Tetsuya; Ikenaka, Yasuhiro; Yajima, Kazuyoshi; Fukao, Hideharu; Ueshima, Shigeru; Matsuo, Osamu (Thrombosis and Haemostasis, 1992)
Tissue-type plasminogen activator (t-PA) is a fibrin-specific agent which has been used to treat acute myocardial infarction. In an attempt to clarify the determinants for its rapid clearance in vivo and high affinity for fibrin clots, we produced five variants containing amino acid substitutions in the finger domain, at amino acid residues 7–9, 10–14, 15–19, 28–33, and 37–42. All the variants had a prolonged half-life and a decreased affinity for fibrin of various degrees. The 37–42 variant demonstrated about a 6-fold longer half-life with a lower affinity for fibrin. Human plasma clot lysis assay estimated the fibrinolytic activity of the 37–42 variant to be 1.4-fold less effective than that of the wild-type rt-PA. In a rabbit jugular vein clot lysis model, doses of 1.0 and 0.15 mg/kg were required for about 70% lysis in the wild-type and 37–42 variant, respectively. Fibrinogen was degraded only when the wild-type rt-PA was administered at a dose of 1.0 mg/kg. These findings suggest that the 37–42 variant can be employed at a lower dosage and that it is a more fibrin-specific thrombolytic agent than the wild-type rt-PA.